BMI1 REDUCES ATM AND ATR ACTIVATION DURING DNA DAMAGE RESPONSE THROUGH BINDING TO NBS1 AND TOPBP1 - LIN, XIAOZENG (My University, 2017)
DNA damage response (DDR) maintains genome integrity through checkpoint activation and lesion repair. While ATM and ATR are essential in DDR, mechanisms regulating their activation remain unclear. BMI1 is a component of the polycomb repressive complex 1 (PRC1), and contributes to PRC1’s E3 ubiquitin (E3-Ub) ligase activity though binding the catalytic subunit RING2. BMI1 binds RING2 through its ring finger (RF) domain. The E3-Ub ligase activity contributes to BMI1-deirved facilitation of the homologous recombination-based repair of DNA double-stranded breaks (DSBs). My research demonstrates that BMI1 reduces ATM and ATR activation during DDR. DSBs and single-strand DNA (ssDNA) lesions respectively activate ATM and ATR. ATM subsequently phosphorylates CHK2 at threonine 68 (CHK2pT68) and induces G2/M arrest. ATR produces CHK1pS345 and S-phase arrest. Both kinases phosphorylate histone H2AX at serine 139 (γH2AX) to prepare for lesion repair. Hydroxyurea initiates DDR via producing ssDNA lesions, and increases ATR activation (phosphorylation of T1989/ATR pT1989), CHK1pS345, γH2AX, and S-phase arrest. These events were significantly reduced and enhanced following the respective BMI1 overexpression and BMI1 knockdown in MCF7 and DU145 cells. BMI1 also displays similar effects towards ATM during DDR induced by etoposide-caused DSBs. Activation of ATM and ATR requires the formation of the ATM-NBS1 and ATR-TOPBP1 complexes. We observed that BMI1 interacted with NBS1 or TOPBP1. Deletion of the RF domain from BMI1 did not affect the associations and also had no effects on BMI1’s activity in reducing ATM activation and ATR-mediated CHK1 pS345. Collectively, our research suggests that BMI1 attenuates ATM and ATR signaling independently of the E3-Ub ligase activity. Genotoxic treatments elicit DDR in cells that are directly exposed and also in cells that are not exposed, a phenomenon known as bystander effect (BE). However, it remains unclear what mediates the BE. Microvesicles are small membrane-enclosed sacks that are shed from donor cells and communicate specific messages to recipient cells. We demonstrated that microvesicles isolated from cells treated with etoposide and ultraviolet induced BE in recipient cells. Neutralization of microvesicles through annexin V reduced the microvesicles-associated BE.
Keywords: BMI1; DNA damage response; ATM and ATR; checkpoint activation; Microvesicles